Hereditary Angioedema with Varied Clinical Presentations: A Case Series - Hamna Hanif; Maha Ahmed; Sabiha Anis (MENA Journal of Case Reports, 2026)
IntroductionHereditary angioedema (HAE) is a rare, potentially life-threatening condition caused by deficiency or dysfunction of C1 esterase inhibitor (C1-INH). It is often misdiagnosed because it clinically resembles other causes of angioedema, such as allergic or acquired forms. Case Series presentationThis paper highlights two cases of adolescent boys with recurrent, non-pruritic angioedema, without associated urticaria. The first patient experienced mild facial edema without identifiable triggers, along with allergic rhinitis. The second patient presented with swelling of the face, lips, and hands, triggered by trauma, and also affecting the airways and abdomen. Family history was significant for a death due to laryngeal edema. Laboratory investigations revealed severely reduced C4 and C1-INH levels in both patients, confirming Type I HAE. DiscussionThese cases demonstrate the variable presentation of HAE, ranging from mild peripheral swelling to abdominal and potentially life-threatening airway involvement. Coexisting allergic disease may lead to confusion with allergic angioedema, while an initially normal C1-INH result may delay diagnosis. Repeat testing and family screening are therefore important when clinical suspicion remains high. Limited access to functional C1-INH testing and targeted therapies remains a major challenge in resource-limited settings. ConclusionThese cases show that HAE may present with mild or severe symptoms and may be overlooked when allergic features are present or when an initial C1-INH result is normal. In resource-limited settings, repeat testing, family screening, and early recognition are important to support diagnosis and prevent serious complications.